2015
DOI: 10.1007/s10874-015-9319-z
|View full text |Cite
|
Sign up to set email alerts
|

Toxic volatile organic air pollutants across Canada: multi-year concentration trends, regional air quality modelling and source apportionment

Abstract: A Unified Regional Air-quality Modelling System, AURAMS, was expanded to predict six toxic volatile organic compounds (VOCs) within a continental domain and two nested domains covering eastern and western Canada. The model predictions were evaluated against Environment Canada's National Air Pollution Surveillance (NAPS) data set to assess the predictive capability of the model at daily and seasonal time scales. The predictions were also evaluated with satellite-derived column total maps for formaldehyde, carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…In the spring-summertime, domain-mean on-road vehicle contributions to ambient BENZ in the GTA were on the order of 14 %-37 %, consistent with, though slightly lower than, previously reported values (Stroud et al, 2016) due to the latter study including off-road mobile sources in their "mobile" category. PAH contributions in the GTA ranged from 5 % to 50 %, depending on species, season, and proximity to major highways.…”
Section: Relative On-road Vehicle Contributionssupporting
confidence: 86%
See 2 more Smart Citations
“…In the spring-summertime, domain-mean on-road vehicle contributions to ambient BENZ in the GTA were on the order of 14 %-37 %, consistent with, though slightly lower than, previously reported values (Stroud et al, 2016) due to the latter study including off-road mobile sources in their "mobile" category. PAH contributions in the GTA ranged from 5 % to 50 %, depending on species, season, and proximity to major highways.…”
Section: Relative On-road Vehicle Contributionssupporting
confidence: 86%
“…The removal of on-road vehicle emissions would lead not only to reductions in ambient benzene and PAH concentrations (as well as in other pollutants), as demonstrated by our model results, but also to reductions in human exposure. Proximity to roadways and traffic has been linked to elevated exposure outdoors, and this has led to particular concerns for commuters (Miao et al, 2015;Yan et al, 2015;Tan et al, 2017;Lovett et al, 2018;Miri et al, 2018). Further inhalation exposure to traffic pollutants occurs in indoor environments, where infiltration of outdoor air can contribute a substantial proportion of benzene and PAH exposure (Naumova et al, 2002;Xu et al, 2016), adding to concerns about residences, schools, and workplaces that are situated near roadways.…”
Section: Human Health Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Column inter-annual variabilities are mainly driven by fire events and temperature changes (Millet et al, 2008;Barkley et al, 2009;Stavrakou et al, 2014). However, over industrialised regions, changes in anthropogenic emissions have also been identified as drivers of observed H 2 CO column trends Zhu et al, 2014;Khokhar et al, 2015;Mahajan et al, 2015;Stroud et al, 2015).…”
Section: Long-term Variationsmentioning
confidence: 99%
“…The lifetime of HCHO in the atmosphere is on the scale of hours to days depending on the levels of ambient oxidants (Seinfeld and Pandis, 2006). Stroud et al (2016) reported on levels of HCHO in Toronto and Egbert, Ontario, and source apportionment. Primary mobile emissions were found to contribute ∼ 12 % of HCHO in Toronto.…”
Section: O 3 No No 2 and Hchomentioning
confidence: 99%